An Insight on the Pathways Involved in Crizotinib and Sunitinib Induced Hepatotoxicity in HepG2 Cells and Animal Model - Guo, Lin; Tang, Tingli; Fang, Dongmei; Gong, Hui; Zhang, Bikui; Zhou, Yueyin; Zhang, Leiyi; Yan, Miao (Frontiers in Oncology, 2022)
Both crizotinib and sunitinib, novel orally-active multikinase inhibitors, exhibit antitumor activity and extend the survival of patients with a malignant tumor. However, some patients may suffer liver injury that can further limit the clinical use of these drugs, however the mechanisms underlying hepatotoxicity are still to be elucidated. Thus, our study was designed to use HepG2 cells in vitro and the ICR mice model in vivo to investigate the mechanisms of hepatotoxicity induced by crizotinib and sunitinib. Male ICR mice were treated orally with crizotinib (70 mg/kg/day) or sunitinib (7.5 mg/kg/day) for four weeks. The results demonstrated that crizotinib and sunitinib caused cytotoxicity in HepG2 cells and chronic liver injury in mice, which were associated with oxidative stress, apoptosis and/or necrosis. Crizotinib- and sunitinib-induced oxidative stress was accompanied by increasing reactive oxygen species and malondialdehyde levels and decreasing the activity of superoxide dismutase and glutathione peroxidase. Notably, the activation of the Kelch-like ECH-associated protein-1/Nuclear factor erythroid-2 related factor 2 signaling pathway was involved in the process of oxidative stress, and partially protected against oxidative stress. Crizotinib and sunitinib induced apoptosis via the mitochondrial pathway, which was characterized by decreasing Bcl2/Bax ratio to dissipate the mitochondrial membrane potential, and increasing apoptotic markers levels. Moreover, the pan-caspase inhibitor Z-VAD-FMK improved the cell viability and alleviated liver damage, which further indicated the presence of apoptosis. Taken together, this study demonstrated that crizotinib- and sunitinib-caused oxidative stress and apoptosis finally impaired hepatic function, which was strongly supported by the histopathological lesions and markedly increased levels of serum alanine aminotransferase, alkaline phosphatase and lactate dehydrogenase.